Jawa Deli Festival: Performance of Javanese Cultural Identity in North Sumatra - Rendina Pradipta (TALENTA Publisher, 2026)
The Javanese ethnic community in Deli, North Sumatra, faces challenges in maintaining cultural practices amid the dynamics of a multicultural society and ongoing social change. These conditions call for revitalization strategies that focus not only on preservation but also on reviving traditions to ensure they remain relevant to younger generations and contemporary society. In this context, cultural festivals serve as vital social spaces for showcasing, negotiating, and transmitting the community’s cultural identity. This study aims to analyze the Deli Javanese Festival as a performative arena that both represents and revitalizes the cultural identity of the Javanese community in diaspora. This study employs a descriptive qualitative approach within the framework of Performance Studies. Research data was collected through direct observation of performance conceptualizers at the festival, in-depth interviews with organizing community groups and artists, information gathering via social media platforms covering festival activities, visual documentation and event archives, as well as a review of relevant references and literature. Analysis was conducted by interpreting the texts and contexts of the performances to understand how performative practices construct cultural meaning, collective memory, and the process of identity negotiation within a multiethnic society. The research findings indicate that the Jawa Deli Festival serves as a cultural space that facilitates both the expression of traditions and the creative adaptation of Javanese arts such as Kuda Lumping, Wayang, and Reog to ensure they remain relevant to a multicultural audience and younger generations. The performances presented serve not only as entertainment but also as a social mechanism that strengthens community cohesion and fosters cultural pride. These findings suggest that festivals can be an effective strategy for cultural revitalization, where traditions are not only preserved but also creatively and adaptively revived so that they remain relevant and sustainable in modern society.